1990
DOI: 10.1037/h0079172
|View full text |Cite
|
Sign up to set email alerts
|

Reported history of physical and sexual abuse and severity of symptomatology in women psychiatric outpatients.

Abstract: Of 140 women outpatients, 64% reported a history of sexual or physical abuse, or both. Symptom checklist scores at the first interview were significantly higher among those reporting a history of recent or childhood abuse than among those reporting no abuse. Implications for further research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(44 citation statements)
references
References 17 publications
(19 reference statements)
9
32
1
1
Order By: Relevance
“…In contrast, only 3% of the CG reported this (p = 0.001). This corresponds to the results of studies which investigated the influence of abuse severity on later behavioral abnormalities and, according to the groupings also used in this study, found a steady increase in frequency of psychological symptoms and social problems from group 0 to 3 [29,30]. Here it is argued that the interaction of several risk factors crucially contributes to a gradual deterioration of the resilience of the children and adolescents involved, making it more difficult to prevent later psychological disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, only 3% of the CG reported this (p = 0.001). This corresponds to the results of studies which investigated the influence of abuse severity on later behavioral abnormalities and, according to the groupings also used in this study, found a steady increase in frequency of psychological symptoms and social problems from group 0 to 3 [29,30]. Here it is argued that the interaction of several risk factors crucially contributes to a gradual deterioration of the resilience of the children and adolescents involved, making it more difficult to prevent later psychological disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, associations have been found between childhood sexual abuse and sleeping disorders, excessive distrust, borderline personality disorder, dissociative disorders, and psychotic symptoms (Boon and Draijer, 1993;Breyer et al, 1987;Kihlstrom et al, 1993;Surrey, et al, 1990). Various studies provide evidence that the effects of childhood sexual abuse depend on individual characteristics of the victims and interpersonal factors at the age of the abuse and later in life (Finkelhor, 1990;Russell, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…There is abundant evidence that victims of childhood sexual abuse are highly at risk of developing physiological and psychological problems (Beitchman et al, 1991;Briere and Runtz, 1988;Brown and Anderson, 1991;Browne and Finkelhor, 1986;Feinauer, 1989;Lange et al, 1995;Palmer et al, 1993;Russell, 1986;Surrey et al, 1990;Williams, 1993;Wozencraft et al, 1991). A review by Finkelhor and Browne (1988) on the long term effects of childhood sexual abuse demonstrated increased risk of sexual disorders, depression, anxiety disorders, auto-mutilation, alcohol-and substance abuse, eating disorders, feelings of isolation and stigmatization, deficiencies in self-esteem, anger towards parents, and prostitution.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Moeller, Bachman, and Moeller (1993) surveyed 668 women and found that 35.6% reported experiencing both CSA and CPA. Surrey, Swett, Michaels, and Levin (1990) found an even higher cooccurrence of 70% for both CSA and CPA. Similarly high cooccurrence rates have been identified by Chu and Dill (1990), Kirby, Chu, and Dill (1993), and Swett and Halpert (1993), who found rates of 66, 82, and 83%, respectively, in their adult samples.…”
Section: Frequency Of Occurrence Of Csamentioning
confidence: 86%